Was It Real? The Exchange Rate‐Interest Differential Relation over the Modern Floating‐Rate Period - MEESE, RICHARD; ROGOFP, KENNETH (Journal of Finance, 1988)
ABSTRACT In this paper, we explore the relationship between real exchange rates and real interest rate differentials in the United States, Germany, Japan, and the United Kingdom. Contrary to theories based on the joint hypothesis that domestic prices are sticky and monetary disturbances are predominant, we find little evidence of a stable relationship between real interest rates and real exchange rates. We consider both in‐sample and out‐of‐sample tests. One hypothesis that is consistent with our findings is that real disturbances (such as productivity shocks) may be a major source of exchange rate volatility.